Peningkatan Kualitas Belajar Siswa Sekolah Dasar Melalui Program Kampus Mengajar - Maharani, Andika Ellena Saufika Hakim; Sari, Baiq Nadia Ulfa; Hisda, Laylatul; Wulandari, Maelina Widia; Hafidah, Nur; Nurkhaliza WR, Siti (Puslitbang Sekawan Institute Nusa Tenggara, 2025)
This article discusses community service through the Teaching Campus Program at SDN 4 Mataram with the aim of improving the quality of student learning. This program was chosen due to the challenges of improving the quality of education at the primary level which still requires innovative interventions. The method applied involves students as facilitators in supporting teachers, developing lesson plans, and developing interesting learning media. Evaluation is conducted through tests and observations to measure student progress. The results show significant improvements in student motivation and understanding, as well as students' ability to apply educational theory in the field. The program also strengthened the relationship between the school and the academic community. In conclusion, collaboration between higher education institutions and elementary schools through the Teaching Campus Program has a significant positive impact on the quality of learning and competency development of the various parties involved.